PENENTUAN TOTAL FENOLIK, FLAVONOID DAN UJI AKTIVITAS ANTIOKSIDAN EKSTRAK DAN FRAKSI DAUN KEDABU (Sonneratia ovata Backer) - Mustika Furi; Nursinta Al Basit; Ihsan Ikhtiarudin; Rahayu Utami (Pengurus Pusat Ikatan Apoteker Indonesia, 2020)
Kedabu (Sonneratia ovata Backer) is plant that belongs to family Lytheraceae which has been used as traditional medicine. Determination of total phenolic and total flavonoid content as well as antioxidant activity of extract and fractions of its leaves have been conducted by colorimetric method using photometric measurements. The Folin Ciocalteu and gallic acid was used as reagent and standard for total phenolic determination, meanwhile AlCl3 and quercetin was prepared for total flavonoid content test. Antioxidant activity assay was performed using DPPH free radical scavenging method. Based on the result, it showed that ethyl acetate fraction afforded the highest total phenolic and total flavonoid content with values of 232 mgGAE/g and 180 mgQE/g, respectively. As for the antioxidant activity, the ethyl acetate fractions also demonstrated the most potential activity among others fraction and extract with IC50 value of 12,47 µg/mL.